Write an expression to represent the sum of three consecutive even numbers. Let C represent the first number in the series
2 answers:
Let, the first number = C
second number will be = C + 2 ['cause next will be odd so we can't include that]
Third number = C + 4
Now, their sum would be:
C + C+2 + C+4 = 3C + 6
In short, Your Answer would be 3C + 6
Hope this helps!
Consecutive even integers would differ by 2.
So if the first even integer is C,
The next is C + 2
The next after is C + 2 + 2 = C + 4
The sum of the three consecutive integers = C + (C + 2) + (C + 4)
C + C + 2 + C + 4
C + C + C + 2 + 4
3C + 6
Sum = 3C + 6
Hope this helps.
You might be interested in
Answer:
648
Step-by-step explanation:
Answer A 7.6 earthquake is more than 2x more powerful than a 3.2
Step-by-step explanation:
Answer:
C
Step-by-step explan:
I rlly hope this is right im sorry if its not.
Y intercept is (0,3)
Slope is 3/2
20 minutes 60minutes ÷ 30miles = 20minutes